Bacterial survival rate on toothbrushes and their decontamination with antimicrobial solutions Taxa de sobrevivência bacteriana em escovas dentais e sua descontaminação com soluções antimicrobianas - Sandra Sato; Izabel Yoko Ito; Elza Helena Guimarães Lara; Heitor Panzeri; Rubens Ferreira de Albuquerque Junior; Vinícius Pedrazzi (University of São Paulo, 2004)
The purpose of this study was to evaluate bacterial survival rate on toothbrushes after brushing and the efficacy of their decontamination by spraying antimicrobial solutions. Thirty subjects were instructed to spray the solutions on toothbrush bristles after brushing. Each volunteer tested three sprays, one solution per week; the sprays were labeled spray 1 (cetylpyridinium chloride - CPC - and basic formulation), 2 (basic formulation only) and 3 (control - sterile tap water). At the end of each week, the brushes were collected and sonicated in Letheen Broth®; the suspensions were ten-fold diluted and the dilutions were plated on various culture media. Anaerobic bacteria, evaluated by colony count of black pigment producing organisms on Ask medium, were recovered from 83.3% of the samples, Streptococci from 80% and aerobic Gram-negative bacilli from 46.7% of them in the control tests. There was a significant decrease in toothbrush contamination with antimicrobial sprays 1 and 2, the first showing the greatest decrease on bacterial counts. O propósito deste estudo foi avaliar a taxa de sobrevivência bacteriana em escovas dentais após a escovação e a eficácia na sua descontaminação pelo borrifamento de soluções antimicrobianas. Trinta indivíduos foram instruídos a borrifar as soluções nas cerdas das escovas após a escovação. Cada voluntário testou três sprays, uma solução por semana; os sprays foram rotulados spray 1 (cloreto de cetilpiridínio - CCP - e formulação básica), 2 (formulação básica apenas) e 3 (controle - água de torneira esterilizada). Ao final de cada semana, as escovas eram recolhidas e introduzidas no caldo Letheen®, submetidas a ultra-som, à diluição decimal seriada e as suspensões semeadas em vários meios de cultura. As bactérias anaeróbias, avaliadas pela contagem de colônias de microrganismos produtores de pigmento negro no meio Ask, foram recuperadas em 83,3% das amostras, estreptococos em 80% e bacilos aeróbios Gram-negativos em 46,7% das amostras nos testes controle. Houve uma significante redução na contaminação das escovas dentais com os sprays antimicrobianos 1 e 2, o primeiro mostrando maior redução nas contagens de bactérias.